2021
DOI: 10.1007/s40122-021-00265-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Continuous Thoracic Paravertebral Infusion of Methylene Blue in the Treatment of Postherpetic Neuralgia: A Prospective, Randomized, Controlled Study

Abstract: Introduction: Postherpetic neuralgia (PHN) is the most common complication of herpes zoster. Methylene blue (MB) is an inhibitor of nitric oxide synthesis with potentially analgesic and anti-inflammatory properties. Studies have demonstrated that thoracic paravertebral single MB injection is effective in treating chronic pain. However, there are rare reports of the efficacy of continuous thoracic paravertebral infusion of MB for pain management in PHN patients. The purpose of this study was to evaluate the the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
0
8
1
Order By: Relevance
“…Preoperative morphine hydrochloride extended-release tablets were used for pain control. Some prevalence studies have reported [ 38 ] that the prevalence of herpes zoster neuralgia is higher in women than in men, which is not consistent with the results of this study, which may be related to the small sample size selected for this trial to be verified by increasing the sample size subsequently.…”
Section: Discussioncontrasting
confidence: 93%
“…Preoperative morphine hydrochloride extended-release tablets were used for pain control. Some prevalence studies have reported [ 38 ] that the prevalence of herpes zoster neuralgia is higher in women than in men, which is not consistent with the results of this study, which may be related to the small sample size selected for this trial to be verified by increasing the sample size subsequently.…”
Section: Discussioncontrasting
confidence: 93%
“…Patients' sleep, emotional disorders, and satisfaction were evaluated using the ISI, HAD, and a five-point Likert scale, respectively. These evaluations have been adopted by many PHN studies (27,28) and can accurately assess patients' status in a scientific and reasonable way. The results of this study showed that patients in group B had lower HAD scores than those in group A 1 week after surgery (p < 0.05), and group B's ISI scores were superior to group A's scores at 1 day, 1 week, 1 month, 3 months, and 6 months after surgery (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, oral or intravenous opioids, nonsteroidal anti-inflammatory drugs, and other multimodal analgesia are often used to treat pain after hemorrhoidectomy ( 4 ), but many patients still feel obvious pain after surgery ( 5 ). Methylene blue can prevent nerve conduction and has strong analgesic, anti-inflammatory, and neurophilic properties ( 6 ). In recent years, methylene blue has been used to treat post-hemorrhoidectomy pain ( 7 ), postherpetic neuralgia ( 8 ), intractable anal pruritus ( 9 ), and other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, methylene blue has been used to treat post-hemorrhoidectomy pain ( 7 ), postherpetic neuralgia ( 8 ), intractable anal pruritus ( 9 ), and other diseases. However, the concentration of methylene blue is still not uniform ( 6 9 ). There have been few reports on the effects of different concentrations of methylene blue on hemorrhoidectomy pain.…”
Section: Introductionmentioning
confidence: 99%